The Effects of Learning Implimentation Based on K-W-D-L Technique on Mathematical Problem-Solving Ability and Learning Achievement of Mathayom Suksa 1 Students - Sriarka, Songpon; Khamrat, Nives (Journal of Graduate Research, 2021)
The objectives of this research were to compare Mathayom Suksa 1 students’ problem-solving ability after learning through K-W-D-L technique against the 70% criterion, to compare their mathematical learning achievement before and after learning through the technique and to compare their mathematical learning achievement after learning through the technique against the 70% criterion. The multi-stage random sampling method was applied to select 20 Mathayom Suksa 1 students from a school under the Secondary Education Service Area Office 42 in the first semester of the 2020 academic year. The research instruments consisted of the lesson plans based on K-W-D-L technique, the problem-solving ability assessment, and the learning achievement test. The data were statistically analyzed for mean, standard deviation, t-test for dependent samples and t-test for one sample.The research results revealed that the students’ mathematical problem-solving abilities after learning through the technique were higher than the 70% criterion, which was statistically significant at the .05 level. It was also found that their learning achievement was higher than the 70% criterion, which was statistically significant at the .05 level.